Evaluation of the Frequency of Tentorial Hypoplasia and Accompanying Gyral Herniation using MRI - Turan, Aynur; Kaplanoğlu, Hatice; Akdağ, Tuba; Yıldırım, Ferhat; Güven, Selda; Hekimoğlu, Baki (Current Medical Imaging, 2024)
PurposeThe cerebellar tentorium, the second-largest dural reflection in the brain, separates supratentorial and infratentorial structures. This study aimed to determine the frequency of tentorial hypoplasia (TH) and gyral herniation and their relationship with clinical findings.MethodsThe standard brain MRIs were examined retrospectively. The presence of TH and laterality were investigated. If hypoplasia was accompanied by a gyrus extending inferior to the line where the tentorium should be located, this was recorded as tentorial hypoplasia-herniated gyrus (TH-HG), while the cases with hypoplasia alone were noted as isolated TH. It was also determined which gyrus or gyri were herniated. The clinical findings of the patients were obtained, and the correlation between HG was explored.ResultsStandard brain MRIs of the 2051 patients were evaluated. Two hundred ten patients were excluded from the study due to different intracranial disorders, and 1841 patients, 739 (40.1%) males, and 1102 (59.9%) females, were included. Isolated TH or TH-HG was present in 56 patients, resulting in a prevalence of 3.04%. Of the patients with TH or TH-HG, 15 were men, and 41 were women. TH and TH-HG were significantly more common in women (p=0.038). TH-HG was unilateral in 22 (39.2%) patients and bilateral in 21 (37.5%). Left TH was found in 11 (19.6%) patients, left TH-HG in 29 (51.7%), right TH in eight (14.2%), and left TH-HG in 35 (62.5%).ConclusionHypoplasia of the tentorium is a rare and unknown anomaly that can be easily diagnosed using MRI, and different gyral herniations may accompany TH.
Keywords: Tentorial hypoplasia